The Discriminants of Long and Short Duration Failures in Fulfillment Sortation Equipment - Mutemi, Abed (2023)
Mutemi, A., Bação, F. (2023). The Discriminants of Long and Short Duration Failures in Fulfillment Sortation Equipment: A Machine Learning Approach. Journal of Engineering, 2023. https://doi.org/10.1155/2023/8557487